Population size estimation of female sex workers in Iran: Synthesis of methods and results. - Hamid Sharifi; Mohammad Karamouzian; Mohammad Reza Baneshi; Mostafa Shokoohi; AliAkbar Haghdoost; Willi McFarland; Ali Mirzazadeh (PLoS ONE)
Introduction Estimating the number of key populations at risk of HIV is essential for planning, monitoring, and evaluating prevention, care, and treatment programmes. We conducted this study to estimate the number of female sex workers (FSW) in major cities of Iran. Methods We used three population size estimation methods (i.e., wisdom of the crowds, multiplier method, and network scale-up) to calculate the number of FSW in 13 cities in Iran. The wisdom of the crowds and multiplier methods were integrated into a nationwide bio-behavioural surveillance survey in 2015, and the network scale-up method was included in a national survey of the general population in 2014. The median of the three methods was used to calculate the proportion of the adult female population who practice sex work in the 13 cities. These figures were then extrapolated to provide a national population size estimation of FSW across urban areas. Results The population size of FSW was 91,500 (95% Uncertainty Intervals [UIs] 61,400-117,700), corresponding to 1.43% (95% UIs 0.96-1.84) of the adult (i.e., 15-49 year-old) female population living in these 13 cities. The projected numbers of FSW for all 31 provincial capital cities were 130,800 (95% UIs 87,800-168,200) and 228,700 (95% UIs 153,500-294,300) for all urban settings in Iran. Conclusions Using methods of comparable rigor, our study provided a data-driven national estimate of the population size of FSW in urban areas of Iran. Our findings provide vital information for enhancing HIV programme planning and lay a foundation for assessing the impact of harm reduction efforts within this marginalized population.